HR TECHNOLOGIES: IMPACT ON THE EFFICIENCY OF HR MANAGEMENT IN THE MODERN BUSINESS ENVIRONMENT - VOLIANSKA-SAVCHUK, Lesia; KLIMAS, Vadim (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main HR technologies and their impact on personnel management. The necessity of defining the concept of HR-technology in personnel management is established; possible directions of development of HR-management are determined. The main categories of HR technologies are defined, as organizations are constantly looking for ways to increase the efficiency of their management processes, improve the quality of work with human capital and increase employee satisfaction HR technologies improve employee adaptation to change, ensure high productivity and develop flexible competencies It is designed to help create conditions for the The advantages and challenges associated with the introduction of HR technologies are discussed, as the integration of the latest technologies into HR processes opens up significant opportunities for e The stages of HR technology implementation in companies are identified. It is noted that thanks to artificial intelligence, automation and data-driven tools, HR technologies are completely changing the way companies find, select and hire the best talent, making the work of recruiters easier and helping them find qualified candidates faster. Artificial intelligence, analytics, and mobile integration can be used to optimize processes and make data-driven decisions that benefit the organization and the candidate. In today's business environment, the effectiveness of human resource management is becoming one of the key factors in the success of an organization. The influence of HR technologies on the efficiency of human resource management is determined.
Keywords: HR technologies; digital technologies; automation of HR processes; integration; development trends; HR management; efficiency